2018
DOI: 10.1186/s12879-018-3491-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of HIV prevalence among MSM in Tokyo using self-collected dried blood spots delivered through the postal service

Abstract: BackgroundMen who have sex with men (MSM) are at high risk of HIV infection. However, there are only few data on HIV prevalence in MSM in Japan. The objective of this study was to explore the HIV prevalence in MSM at Shinjuku 2-chome, a well known gay quarter in Tokyo.MethodsMSM directly collected the dried blood spot (DBS) self-collection HIV test kit from a drop-in center in Shinjuku 2-chome between August 2015 and December 2016. The participants collected their own blood by finger-prick and anonymously post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…Most MSM followed the DBS collection and packaging/mailing instructions to provide their own specimens for HIV laboratory-based testing. Our analyses support the self-collection and mailing of DBS as a possible strategy for collecting blood specimens from MSM for HIV testing and treatment monitoring [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 58%
“…Most MSM followed the DBS collection and packaging/mailing instructions to provide their own specimens for HIV laboratory-based testing. Our analyses support the self-collection and mailing of DBS as a possible strategy for collecting blood specimens from MSM for HIV testing and treatment monitoring [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 58%
“…A home sampling testing service may lower barriers to testing, increase testing frequency and thus limit onward transmission. Takano et al showed that ssDBS for HIV testing is an acceptable method for MSM in Tokyo and can improve access to testing for MSM who live in rural areas [21]. Coats and Dillon found evidence that DBS may increase the frequency of HCV testing [30].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies reported the use of ssDBS for determining drug levels [16][17][18][19]. One large Japanese study showed the successful use of ssDBS sent by regular mail for HIV diagnosing HIV using an HIV antigen/antibody test [21].…”
Section: Introductionmentioning
confidence: 99%
“…The minimal invasiveness of sampling and the ease of handling, storing, and transporting DBS offer additional opportunities to reach the first 90% of the 90-90-90 UNAIDS target. This strategy can be applied to highly diverse contexts, including, for instance, the testing of self-collected DBS delivered through the postal service (35,36).…”
Section: Discussionmentioning
confidence: 99%